Evaluation of pier scour reduction using combination of collars, slots and threading method - m m; s a; m sh (مهندسی منابع آب, 2018)
The local scour around the piers is an important factor that causes of the destruction of the bridges. Therefore, to avoid this phenomenon there is scientific solutions to protect the pier against scour. some of the most effective techniques you can use ,are using the collars or threading or slots on the pier. Therefore using the slots is not practical or not suitable to consider as permanent solution and threading is not so effective method so there is an idea to compose threading and slots with collars together in this experimental work that can make slots and threading so more practical and useful in pier scour reduction . there have been created some new tools which name jet-collar , slot-veneer and thread-veneer. at the best condition results shows that some of the collars which have a jagged side as a jet and a collar at other side , so this jet-collar could reduce local scour by 83% at pier side.